The approach of value innovation towards superior performance, competitive advantage, and sustainable growth: A systematic literature review - Hajar M.A.; Alkahtani A.A.; Ibrahim D.N.; Darun M.R.; Al-Sharafi M.A.; Tiong S.K. (MDPI, 2023)
economic growth; empirical analysis; innovation; literature review; methodology; strategic approach; sustainability